PENGARUH SIKAP TOLERANSI DAN LINGKUNGAN BELAJAR TERHADAP SIKAP MODERASI BERAGAMA MELALUI PEMBELAJARAN FIQIH - Hafilda Anisa; Nia Rosita; Alwaris Syam; Uus Ruswandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of tolerance attitudes and learning environments on students' attitudes toward religious moderation in Fiqh learning at a boarding school in Subang Regency. The research problem stems from the phenomenon of low religious moderation practices among adolescents, even though a formal religious curriculum has been implemented. Intolerant attitudes and rigid religious understanding are still found in social and learning interactions. This study uses a quantitative approach with multiple linear regression method. Data were collected through questionnaires that had been tested for validity and reliability, involving 86 respondents from grades VII, VIII and IX. The results of the analysis show that both tolerance attitudes and learning environments have a significant effect on religious moderation attitudes. Partially, both independent variables contribute positively to the understanding and application of moderation values in the context of Fiqh learning. Simultaneously, tolerance and learning environment influence religious moderation attitudes by 62.9%, while the rest is influenced by other factors. These findings confirm that education on tolerance and the creation of a conducive learning environment need to be prioritized as part of a strategy to strengthen religious moderation in schools. This study recommends the integration of moderation values into the curriculum and dialogical learning methods to encourage students to be more open, wise, and respectful of diversity.